The Neural and Cognitive Mechanisms of Knowledge Attribution : An EEG Study - Bricker, Adam (My University, 2020)
Despite the ubiquity of knowledge attribution in human social cognition, its associated neural and cognitive mechanisms are poorly documented. A wealth of converging evidence in cognitive neuroscience has identified independent perspective-taking and inhibitory processes for belief attribution, but the extent to which these processes are shared by knowledge attribution isn’t presently understood. Here, we present the findings of an EEG study designed to directly address this shortcoming. These findings suggest that belief attribution is not a component process in knowledge attribution, contra a standard attitude taken by philosophers. Instead, observed differences in P3b amplitude indicate that knowledge attribution doesn’t recruit the strong self-perspective inhibition characteristic of belief attribution. However, both belief and knowledge attribution were observed to display a late slow wave widely associated with mental state attribution, indicating that knowledge also shares in more general processing of others’ mental states. These results provide a new perspective both on how we think about knowledge attribution, as well Theory of Mind processes generally.
Keywords: Theory of Mind, Mentalizing, Perspective Taking, Self-Perspective Inhibition, Knowledge-First, Epistemology